A New Look at the Electronic Structure of Transparent Conductive Oxides—A Case Study of the Interface between Zinc Magnesium Oxide and Cadmium Telluride. Issue 22 (20th September 2016) - Duncan, Douglas A.; Mendelsberg, Rueben; Mezher, Michelle; Horsley, Kimberly; Rosenberg, Samantha G.; Blum, Monika; Xiong, Gang; Weinhardt, Lothar; Gloeckler, Markus; Heske, Clemens
Abstract : By combining X‐ray and ultraviolet photoelectron spectroscopy, X‐ray excited Auger electron spectroscopy, and inverse photoemission spectroscopy, a detailed characterization of the chemical and electronic structure at the CdTe/(Zn, Mg)O interface is presented. In doing so, a novel approach to characterize the electronic structure of transparent conductive oxides, namely, to distinguish between optically and transport‐relevant states is presented. Consequently, "optical" and "electronic" band offsets at the CdTe/(Zn, Mg)O interface are derived and it is demonstrated that the "electronic" band offset is suitable for electron transport across the interface (a flat conduction band alignment of 0.02 ± 0.20 eV), while the "optical band offset" is not (a significant 0.48 ± 0.20 eV spike). The new approach can easily be applied to many other transparent conductive oxides and is thus of relevance for a large variety of optoelectronic applications involving transparent electrical contacts. Abstract : A novel approach to characterize the electronic structure of transparent conductive oxides, namely, to distinguish between optically and transport‐relevant states is presented. Consequently, "optical" and "electronic" band offsets at the CdTe/(Zn, Mg)O interface are derived and it is demonstrated that the "electronic" band offset is suitable for electron transport across the interface (a flat conduction band alignment of 0.02 ± 0.20 eV), while the "optical band offset" is not (a significant 0.48 ± 0.20 eV spike).